Detection of temporomandibular disorders in students of Franklin Roosevelt Private University of Huancayo – 2018 - Cueva Buendía, Luis Alberto (2020)
Objectives: To describe the temporomandibular disorders, most prevalent, according to the Helkimo index in the students of Franklin Roosevelt, private university of Huancayo, evaluated at the beginning of the academic semester 2018-I. Material and Methods: we used the scientific method in general and the observational in specific cases. Type of basic research simple descriptive design was used. The population was 2276 students from I to X cycle of both sexes and enrolled in their respective cycles, belonging to the professional schools of the private university of Huancayo Franklin Roosevelt. The sample was 329 selected students with stratified probabilistic sampling. Data collection was carried out through the observation technique and the instrument the clinical record through the Helkimmo test. The methods used for data analysis and processing were through the SPSS V 20 software and Excel 2010. Results: The results were presented in tables, charts and graphs of frequencies and percentages. It was evidenced that “moderate disorder” reached 55.9% of the sample, the “severe disorder grade I” reached 38.9 %, with “normal function” the 2.4%, “severe disorder grade III” the 1.2%, “grade II severe disorder 0.9% and mild disorder 0.6%. Conclusions: It has been found in the detection of temporomandibular disorders, that “moderate disorder” is the most prevalent with 55.9 percent of the sample, followed by “severe disorder grade I” with 38.9 percent, in students of Franklin Roosevelt private University of Huancayo, evaluated in the academic semester 2018-I, with the Helkimo test.